Coexistence of rapidly resolving acute subdural hematoma and delayed traumatic intracerebral hemorrhage - Erol, FS; Kaplan, M; Topsakal, C; Ozveren, MF; Tiftikci, MT (Karger, 2004)
Rapid resolution of acute subdural hematoma is rare. Delayed traumatic intracerebral hematomas following medical or surgical treatment of increased intracranial pressure have also been reported. Coexistence of a quickly resolving acute subdural hematoma and a delayed traumatic intracerebral hemorrhage has not been reported before. A 13-month-old boy was admitted to our emergency department after a car accident. On CT, a thin acute subdural hematoma on the right frontotemporal region and a small epidural hematoma on the left frontal region could be seen. On 24-hour follow-up CT, the right subdural hematoma was found to be less dense but larger than it had been before. At 36 h after hospitalization, CT showed that the right acute subdural hematoma had completely disappeared; however, a delayed traumatic intracerebral hematoma on the left occipital region was identified. We think that the mechanism involved in the development of a delayed intracerebral hematoma in our case was similar to the one causing delayed traumatic intracerebral hematoma after treatment for increased intracranial pressure. Copyright (C) 2004 S. Karger AG, Basel.
Keywords: delayed traumatic intracerebral hemorrhage; subdural hematoma